DONALD CRESSEY’S THEORY PADA ACADEMIC FRAUD MAHASISWA BISNIS DAN KEUANGAN - ALPIANSAH, RESTU; KOMALA, RINA; RAMDANI, RIZAL (Universitas Mahasaraswati K. Mataram, 2023)
Donald Cressy's theory states that pressure, opportunity, and rationalization can drive a person to commit fraud. The theoretical concept is packaged in the concept of the fraud triangle theory. This study aims to test this theory using 89 respondents who come from business and finance students at University XYZ. This study used a quantitative approach by collecting data using a questionnaire. The study results show that only rationalization factors partially influence student academic fraud. However, if tested simultaneously, the three factors in Donald Cressy's theory are proven to have an influence that can encourage students to commit acts of academic fraud